Over-Time Trends in Incivility on Social Media: Evidence From Political, Non-Political, and Mixed Sub-Reddits Over Eleven Years - Sun, Qiusi; Wojcieszak, Magdalena; Davidson, Sam (Frontiers in Political Science, 2021)
Incivility in social media has become a major concern of the public, who perceive uncivil online interactions to be both widespread and increasing. This study provides a descriptive account of incivility dynamics over the past 11 years by examining the trends of incivility in three main categories of social media interactions: political, mixed, and non-political. Using longitudinal data from Reddit that accounts for 95% of the entire Reddit universe across 11 years and relying on the combination of supervised machine learning models and traditional statistical inference, the study found that incivility consistently represents around 10% of total Reddit comments. Additionally, political groups tend to be more uncivil, and discussions in mixed groups that are not overtly political but nevertheless discuss politics are less uncivil than in political groups. We also found that the fluctuations of incivility correspond to offline events and platform-specific policies.